Pandangan Salah Umat Maitreya Terhadap Pola Hidup Vegetarian - Tjoa Holyenty (Dhammavicaya : Jurnal Pengkajian Dhamma, 2023)
Religion has an important role in a person's life, setting limits on what can and cannot be done. Maitreya Buddhism teaches its people to imitate Maitreya Buddha as a vegetarian. And because of this, people often think that Maitreya Buddhists must be vegetarians. Although in reality this opinion is not always true. In this study, the author will discuss the wrong view of Maitreya Buddhists on the vegetarian lifestyle. Why have long been a follower of Maitreya Buddhism but not a vegetarian. The author wants to know how deep the understanding of the followers of Maitreya Buddhist teachings at the Jelambar monastery on the vegetarian lifestyle. The author hopes that through this research, readers can better understand the importance of vegetarianism for themselves and as followers of Maitreya Buddhism.